Dampak Digitalisasi terhadap Peningkatan Produktivitas Usaha Mikro Kecil, Menengah (UMKM) di Era Ekonomi Digital Kota Kefamenanu - Aurelia Inacia Noyola N. Da Gama; Fransina W. Ballo; Maria Indriyani Hewe Tiwu (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
This study aims to analyze the impact of digital technology implementation on increasing the productivity of MSMEs in Kefamenanu City in the digital economy era. Digitalization is examined through the adoption of digital marketing, the use of e-commerce platforms, and the application of electronic payment systems or e-payments. Meanwhile, MSME productivity is assessed based on operational efficiency, market reach, and increased sales volume. This study uses a qualitative descriptive method, with data collected through observation, interviews, and documentation involving MSME actors who have applied digital technology in their business activities. The results indicate that digitalization has a positive impact on MSME productivity in Kefamenanu City by helping business owners promote products more widely, simplify transactions, improve service speed, and expand consumer access. Nevertheless, the implementation of digital technology still faces several challenges, including limited digital network infrastructure in certain areas and low digital literacy among some micro-business owners. Therefore, training and infrastructure support are needed to strengthen MSME competitiveness in the digital economy era and support sustainable local economic growth.